2013
DOI: 10.1310/hpj4804-302
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Pharmacist-Driven Protocol to Improve Drug Allergy Documentation at a University Hospital

Abstract: Background: An internal evaluation of the inpatient pharmacy order entry database (WORx) at a university hospital revealed that the nature of the reaction was documented for only 47% of patients with reported drug allergies/intolerance. Insufficient documentation of drug allergy/intolerance may result in administration of drugs that should not be prescribed. Similarly, valuable agents that should be used may not be prescribed due to an unnecessary fear of adverse drug reaction. More complete description of dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 8 publications
(17 reference statements)
0
13
0
Order By: Relevance
“…In 1964, Mills addressed the importance of capturing information on allergies and drugs, proposing a new checklist that served as a guideline in hospitals [ 31 ]. A similar initiative was taken more recently by Burrell et al [ 32 ], who introduced a pharmacist-driven protocol in a hospital to improve the completeness of DA or intolerance documentation. A review of medical notes in a general district hospital demonstrated poor documentation practices where 97.4% (114/117) of drug allergy boxes were only partially completed and 2.6% (3/117) had nothing documented [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…In 1964, Mills addressed the importance of capturing information on allergies and drugs, proposing a new checklist that served as a guideline in hospitals [ 31 ]. A similar initiative was taken more recently by Burrell et al [ 32 ], who introduced a pharmacist-driven protocol in a hospital to improve the completeness of DA or intolerance documentation. A review of medical notes in a general district hospital demonstrated poor documentation practices where 97.4% (114/117) of drug allergy boxes were only partially completed and 2.6% (3/117) had nothing documented [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Systematic reconciliation together with appropriate evaluation of reported ADR will improve the accuracy and completeness of documentation within EHR. Pharmacist‐led initiatives have shown promise in improving the completeness of ADR documentation, identifying discrepancies between the patient's medical records and performing further evaluation of documented ADR . There are opportunities for dedicated clinical services to manage the documentation of ADR in the hospital setting.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacist-led initiatives have shown promise in improving the completeness of ADR documentation, identifying discrepancies between the patient's medical records and performing further evaluation of documented ADR. [30][31][32] There are opportunities for dedicated clinical services to manage the documentation of ADR in the hospital setting. Health institutions should implement diagnostic pathways to combat the accumulation of ADR labels over a patient's lifetime.…”
Section: Discussionmentioning
confidence: 99%
“…In a BPMH, a patient's medication list and list of allergies and ADRs are corroborated with prescription pill containers, as well as family, outpatient pharmacy, and primary care physician input [17]. Previous research has shown that involvement of the pharmacy team in the medication reconciliation process is effective in reducing discrepancies in the medical record, sometimes more so than physician-or nurse-led efforts [10,18,19]. Better allergic reaction and ADR documentation platforms in the EMR may also reduce discrepancy rates, particularly if outpatient and pharmacy records can be seamlessly integrated.…”
Section: Discussionmentioning
confidence: 99%